Debye temperature of wurtzite AlN determined by X-ray powder diffraction. Issue 4 (14th July 2014) - Wang, J.; Zhao, M.; Jin, S. F.; Li, D. D.; Yang, J. W.; Hu, W. J.; Wang, W. J.
<x content-type="archive" xml:space="preserve">Abstract</x> The Debye temperature of wurtzite aluminum nitride (AlN) was determined by the Rietveld refinement method based on the room-temperature X-ray powder diffraction data. The refined lattice parameters are a = 3.11139(1) Å, c = 4.978 43(3) Å; the refined positional parameter for N is z = 0.384 59(33) Å; and the refined temperature factors of Al and N were 0.442(12) Å2 and 0.559(33) Å2, respectively. Using this refined temperature factor, the Debye temperature was evaluated as 971 K through the Debye approximation.